Investigating the Impact of Family Drug and Alcohol Courts on Parental Reunification and Offending: A Data Linkage Study - Alrouh, Bachar; Harwin, Judith; Hargreaves, Claire; Humphreys, Leslie; Barlow, Charlotte (International Journal of Population Data Science, 2025)
Family Drug and Alcohol Courts (FDACs) are a type of problem-solving court, which uniquely both treat parental problems and adjudicate. This study investigates whether FDACs improve family reunification rates and their sustainability compared to ordinary care proceedings, and reduce parental offending. This presentation will evaluate the feasibility of linking administrative datasets from FDAC, Cafcass, and the Police National Computer (PNC) to create a novel cross-justice linked data asset. In this ESRC-funded study, we have successfully linked individual-level records from FDAC case files, Cafcass and the PNC, creating a longitudinal dataset of approximately 6,500 parents. Deterministic and probabilistic linkage techniques ensured accurate matching while minimising linkage error. Linkage quality was assessed through match rates, data completeness, and variable consistency. The final dataset enables longitudinal analysis of reunification rates and their sustainability (measured by recurrence of care proceedings), followed by parental offending trajectories. Data quality assessments explore challenges and best practices in linking justice and family court records. The data linkage process was conducted in several stages. First, person and case identifiers were collected from FDAC case files and successfully linked to Cafcass records. Matching criteria based on demographic and case characteristics were then established, and the matched comparison group was selected from ordinary care proceedings, ensuring comparability with the FDAC sample. Finally, the combined FDAC and comparison cohorts were linked to the Police National Computer (PNC) to obtain offending histories. Linkage success rates were high across all stages, with minimal missing data. These results demonstrate the feasibility of integrating sensitive administrative datasets, highlighting best practices in cross-sector record linkage and establishing a foundation for future research on justice and family court interventions. This study demonstrates the feasibility and value of linking administrative data to evaluate FDACs’ impact on family reunification and parental offending. By integrating justice and family court records, it establishes a framework for future research, informing evidence-based policy decisions on problem-solving courts and their role in promoting family stability and reducing reoffending.